Coaching leadership style and personality trait among coaches-athlete Malaysian successful and less successful football teams / Abbylolita Sullah - Sullah, Abbylolita (2015)
In order to optimize team’s performance, preferred coaching leadership style and personality trait could be the main factors. A total of 16 coaches and 200 players of Malaysia Super League and Malaysia Premier League have completed Leadership Scale for Sport (LSS, 1980) and Graduate Employability Questionnaire (GEQ, 2009) which LSS consisted of Training and Instruction (TI), Democratic Behaviour (DB), Autocratic Behaviour (AB), Social Support (SS), Positive Feedback (PF) and GEQ consisted of Personal Attributes and Personal Qualities. This study found that Malaysian successful and less successful football teams showed means of TI, DB, AB, SS and PF with means (M=4.25; M=4.15; M=2.51; M=4.10; M=4.13), (M=4.30; M=4.21; M=2.51; M=4.20; M=4.22) respectively. Subsequent for the personality traits, the results showed that the personal attributes and personal qualities for coaches of less successful football teams had the higher mean score of (M=4.43) and (M=4.56) as compared to the coaches’ personal attributes and personal qualities of successful football teams (M=4.33) and (M=4.29).Similarly, players from the less successful teams showed superior mean score for personal qualities (M=4.32) and personal attributes (M=4.24) than the players from the successful teams (M=4.17) and (M=4.09). Pearson correlation has done with coaches and players demographic variables with coaching leadership style. As a result, relationships existed between age to Positive Feedback (r = .197, n = 100, p < .05) as well marital status to Positive Feedback (r = .266, n = 100, p < .05) in successful football teams.Whereas, in less successful football teams, there were relationships occurred between race to Training and Instruction (r = .367, n = 100, p < .05), race to Democratic Behaviours (r = .239, n = 100, p < .05) as well years of participation to Democratic Behaviours (r = .280, n = 100, p < .05). Moreover, multiple regression predicted that age, level of competition/coaching certification and year of participation could be the most influential factors on coaches and players’ achievement with statistical result supported: t (216) = 8.244; p < .05, t (216) = 2.058; p < .05 and: t (216) = 38.151; p < .05. In addition,the independent t-test examined that there is a significant difference between the personality traits of the players and those coaches n (214); t = 2.441, p = .015; <.05, n (214); t= 2.434, p = .020; <.05 as well there is significant difference for both Malaysian successful and less successful football teams in personal qualities with the statistical reading of n (106); t = 4.947, p = .000; <.05. Therefore, this result implicated that coaching leadership style preferences are varies due to differences in players’ ages as well as different levels of experience which encounter prolonged periods of success or failure of a team and these contributed to coaching science, the body of knowledge.